2000
DOI: 10.1046/j.1432-1327.2000.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of α, β and γ enolase isoforms in regenerating mouse skeletal muscle

Abstract: Nothing is known about the expression of the glycolytic enzyme enolase in skeletal muscle alterations such as myofiber degeneration and regeneration. Enolase is a dimeric enzyme which exhibits cell type specific isoforms. The embryonic form, aa, remains expressed in most adult tissues, whereas a transition towards specific isoforms occurs during ontogenesis in two cell types with high energy requirements: ag and gg in neurons, ab and bb in striated muscle cells. During murine myogenesis, b enolase transcripts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 44 publications
2
45
0
Order By: Relevance
“…We observed that the perinuclear immunoreactivity of β-enolase in the rat sarcoma cells was more intensive than in normal rat cells. This corresponds to other reports on the localization of mouse muscle enolase in regenerating tissue [1]. However other authors report a nuclear location of enolase molecules in rat neurons [21] and HeLa cells [22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that the perinuclear immunoreactivity of β-enolase in the rat sarcoma cells was more intensive than in normal rat cells. This corresponds to other reports on the localization of mouse muscle enolase in regenerating tissue [1]. However other authors report a nuclear location of enolase molecules in rat neurons [21] and HeLa cells [22].…”
Section: Discussionsupporting
confidence: 91%
“…The ubiquitous αα isoform remains widely distributed in embryonic most adult cell types. In adult muscle tissues, the β-enolase subunit accumulates preferentially in fast-twitch fibres, where the ββ homodimer accounts for more than 90% of the total enolase activity [1].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with them being products of different genes or for example alternative splice variants, or post translational modifications of the same proteins. Evidence for independently regulated different genes is that multiple genetic isoforms have been reported for arginine kinase (65,66), enolase (67), and ferritin (68,69). For proteasome there are three different subunits in Table III.…”
Section: Biological Variation Is Significant When Compared With Technmentioning
confidence: 99%
“…Neuron-specific enolase (gamma enolase, NSE) is predominantly expressed by neurons and neuroendocrine cells, but much lower levels are also expressed by developing or injured striatal muscle cells, 17 by activated T cells, and by activated macrophages. 18 We initially constructed transgenic animals that overexpress either BMP4 (NSE-BMP4) or the BMP inhibitor noggin (NSEnoggin) under control of the NSE promoter to examine the role of BMP signaling in development of the brain.…”
Section: Young Nse-bmp4 Transgenic Mice Develop Severe Heterotopic Bomentioning
confidence: 99%